Increasing Motivation of Iranian Students to Continue Education in Germany. Challenges and Opportunities in Academia - Zahra Arzjani, (Technium Social Sciences Journal, 2024)
The emigration of educated individuals from Iran has become a prominent and multifaceted issue in recent years, eliciting diverse perspectives. Statistical analysis reveals a substantial surge in the number of Iranian students electing Germany as their preferred destination for higher education. Notably, the count of Iranian students studying in Germany has witnessed a more than threefold increase, soaring from 4,182 students in 2008 to 13,279 in 2023. Moreover, the student population has nearly tripled from 4,182 in 2008 to 11,573 in 2021, signifying a 45% surge compared to the preceding year. This prompts an inquiry into the factors underpinning Iranian students' preference for Germany. To delve into this phenomenon, a survey was conducted among Iranians residing in Germany. The survey outcomes reveal that the deteriorating living conditions in Iran, coupled with Germany's political stability and robust social welfare system, have played pivotal roles in motivating students and university graduates to pursue education abroad. Educational advancement emerges as a secondary consideration in their decision-making process.